2002
DOI: 10.1385/abab:101:3:229
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tween 80 on Lipid Metabolism of an Aspergillus niger Strain

Abstract: Addition of 0.1% of nonionic surface-active Tween 80 to a medium optimized for pectolytic enzyme production of Aspergillus niger increased the amount of enzymes excreted by 70%. In the presence of Tween 80 the amount of sterol esters and triacylglycerols was increased. During the course of cultivation the amounts of precursors for ergosterol biosynthesis diminished with an increase of ergosterol. A. niger incorporated cholesterol from the medium, partly converting it to cholesterol esters. Sterol esters were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We are presently developing a small-scale MIC test using the NCCLS M38-A format, and the preliminary data are consistent with results described here. Our findings, together with the recognition that pathogenic microorganisms differ markedly in their ability to import cholesterol (3,39), have immediate biomedical implications and should foster the development of improved antifungal agents.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…We are presently developing a small-scale MIC test using the NCCLS M38-A format, and the preliminary data are consistent with results described here. Our findings, together with the recognition that pathogenic microorganisms differ markedly in their ability to import cholesterol (3,39), have immediate biomedical implications and should foster the development of improved antifungal agents.…”
Section: Discussionmentioning
confidence: 78%
“…Another possible factor is exogenous sterol uptake. Although uptake of abiotic cholesterol by filamentous fungi is known (3,39), effects of sterol import on antifungal therapy have never been studied. Our results demonstrate that the fungal pathogen A. fumigatus imports cholesterol from medium, a process that is associated with enhanced growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This number was in good agreement with the number obtained for cells eluted with triton X100-supplemented buffer (see above). Since triton X-100 is not a likely carbon/ energy substrate (Zeng et al, 2007), the sharp increase in the number of RSG-stained cells is most probably not due to metabolic activation but due to the surfactant properties of triton X-100, affecting the permeability of the cell membrane (Helenius and Simons, 1975;Nemec and Jernejc, 2002) and facilitating cell penetration by RSG. These results indicated that to use this approach to obtain cells for downstream analysis, including cultivation, a modification of the extraction buffer omitting triton X-100 was necessary to avoid the risk of cell membrane disruption.…”
Section: Resultsmentioning
confidence: 99%